Comparison of material properties of heel pad between adults with and without type 2 diabetes history: An in-vivo investigation during gait - Yang, Xiong-gang; Teng, Zhao-lin; Zhang, Zhen-ming; Wang, Kan; Huang, Ran; Chen, Wen-ming; Wang, Chen; Chen, Li; Zhang, Chao; Huang, Jia-zhang; Wang, Xu; Ma, Xin; et al. (Frontiers in Endocrinology, 2022)
Objective: This study was aimed to compare the material properties of heel pad between diabetes patients and healthy adults, and investigate the impact of compressive loading history and length of diabetes course on the material properties of heel pad. Methods: The dual fluoroscopic imaging system (DFIS) and dynamic foot-ground contact pressure-test plate were used for measuring the material properties, including primary thickness, peak strain, peak stress, stiffness, viscous modulus and energy dissipation ratio (EDR), both at time zero and following continuous loading. Material properties between healthy adults and DM patients were compared both at time zero and following continuous weight bearing. After then, comparison between time-zero material properties and properties following continuous loading was performed to identify the loading history-dependent biomechanical behaviour of heel pad. Subgroup-based sensitivity analysis was then conducted to investigate the diabetes course (<10 years vs. ≥10 years) on the material properties of heel pad. Results: Ten type II DM subjects (20 legs), aged from 59 to 73 (average: 67.8±4.9), and 10 age-matched healthy adults (20 legs), aged from 59 to 72 (average: 64.4±3.4), were enrolled. Diabetes history was demonstrated to be associated with significantly lower primary thickness (t=3.18, p=0.003**), higher peak strain (t=2.41, p=0.021*), lower stiffness (w=283, p=0..024*) and lower viscous modulus (w=331, p<0.001***) at time zero, and significantly lower primary thickness (t=3.30, p=0.002**), higher peak strain (w=120, p=0.031*) and lower viscous modulus (t=3.42, p=0.002**) following continuous loading. The continuous loading was found to be associated with significantly lower primary thickness (paired-w=204, p<0.001***) and viscous modulus (paired-t=5.45, p<0.001***) in healthy adults, and significantly lower primary thickness (paired-w=206, p<0.001***) and viscous modulus (paired-t=7.47, p<0.001***) in diabetes group. No any significant difference was found when conducting the subgroup analysis based on length of diabetes course (<10 years vs. ≥10 years). Conclusions: Diabetes patients were found to be associated with decreased primary thickness and viscous modulus, and increased peak strain, which may contribute to the vulnerability of heel pad to injury and ulceration. Pre-compression history-dependent behaviour is observable in soft tissue of heel pad, with lowered primary thickness and viscous modulus.